2005
DOI: 10.1196/annals.1338.027
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress‐Induced Depolymerization of Microtubules and Alteration of Mitochondrial Mass in Human Cells

Abstract: Mitochondrial biogenesis is a biological process that has been intensively studied over the past few years. However, the detailed molecular mechanism underlying this increase in mitochondria remains unclear. To investigate the mechanism of such a mitochondrial proliferation, we examined alterations in mitochondria of human osteosarcoma 143B cells that had been treated with 100 to 500 microM hydrogen peroxide (H2O2) for 48 h. The results showed that mitochondrial mass of the cell was increased with the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 13 publications
8
76
0
Order By: Relevance
“…The mechanisms responsible for the increased amount of mtDNA in DRHEp2 are unknown. Lee et al (2005) reported that the amount of mtDNA was increased by treatment with paclitaxel or a low dose of hydrogen peroxide in human osteosarcoma cells. They also showed that mitochondria abnormally proliferated in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for the increased amount of mtDNA in DRHEp2 are unknown. Lee et al (2005) reported that the amount of mtDNA was increased by treatment with paclitaxel or a low dose of hydrogen peroxide in human osteosarcoma cells. They also showed that mitochondria abnormally proliferated in cells.…”
Section: Discussionmentioning
confidence: 99%
“…18 In functional studies, exposure to hydrogen peroxide, a reactive oxygen species, resulted in damage to the DNA replication enzyme (polymerase g) in the mitochondria and a reduction in mtDNA copy number. 19,20 Exposure to TNF-a, an inflammatory cytokine, also generated reactive oxygen species and reduced mtDNA copy number in myocytes. 21 Cross-sectional studies of patients with CKD have shown that lower mitochondrial function, indicated by metabolites from urine and gene expression from peripheral blood, correlated with more severe CKD.…”
Section: Main Findingsmentioning
confidence: 99%
“…The availability of the TK1-specific substrate (FLT) TK2-specific substrate (Ara-T), and TK2 inhibitor [bromovynil deoxyuridine (BVDU)] [12][13][14], provided the needed tools to measure the role of TK2 in FMAU retention. Previous experiments with H 2 O 2 and certain antineoplastic treatments have shown to increase mitochondrial DNA and mass [15][16][17][18][19]. These changes were assumed to be due to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%